Методи навчання штучної нейронної мережі - Щербина, Ю. М.; Годич, О. В. (Видавництво Національного університету "Львівська політехніка", 2001)
Contains information about present situation of artificial neural networks learning concepts and methods. Advantages and disadvantages of these methods are analyzed. A new concept is purposed and described as an approach to avoiding known problems of learning with samples and of self-organized structures. Описано сучасний стан у галузі навчання нейронних мереж Пропонується нова концепція і описується підхід до проблем отримання знань з простими і самоорганізаційними структурами.